Eventos extremos de precipitação em Londrina (PR): uma análise multidisciplinar - Leite, Luiza Teodoro (2022)
The possibility of an increase in the occurrence of extreme precipitation events has worried scientists and managers around the world. The adaptation and mitigation of the impacts inherent to these extremes go through a rigorous statistical analysis of the intensity and frequency of their occurrences. In this context, the present research sought to identify trends for extreme precipitation events in the vicinity of Ribeirão Cambé, in the city of Londrina Paraná. There is only one rainfall station available in the basin region, which presented 41 years of complete data without failures. The highest value among the annual precipitation totals occurred in 2015 (2449 mm). The month with the highest average daily rainfall was January (58.05 mm), while the month with the lowest average was August (21.35 mm). The three highest values of outliers were observed in January 2016 with a daily rainfall of 223.6 mm, in June 2012 (200.5 mm) and in June 1997 (161.0 mm). For the annual trend analysis, the Mann Kendall and Pettit tests were applied. A decrease was observed for all indices used that analyzed precipitation extremes, at a significance level of 95%. With regard to the analysis of monthly rainfall trends, few indices showed statistically significant trends. For the analysis of the GEV, it was verified that it is expected that once every 20 years a day occurs when the precipitation is 200 mm at a significance level of 95%. The equation Intensity Duration and Frequency – IDF, was created from the Gumbel maximum distribution and the Disaggregation Method of CETESB (1986). The coefficient of determination (R²), obtained by the relationship between the observed and estimated rainfall intensities by the IDF equation, was 0.9981, allowing its use in locations where there is no availability of rainfall records. Several studies indicate an increase in extreme precipitation throughout the national territory. Given this scenario and considering the lack of planning for land use and occupation, extreme precipitation events are expected to cause serious damage to the urban environment, such as more intense and frequent flooding, in addition to social, environmental and economic risks. Finally, it is essential to prevent and control the impacts of extreme precipitation events from water infrastructure systems.